Making words sing : nineteenth- and twentieth-century song - Dunsby, Jonathan (Cambridge, 2004)
What makes a classical song a song? In a wideranging discussion, covering such contrasting composers as Brahms and Berberian, Schubert and Kurtág, Jonathan Dunsby considers the nature of vocality in songs of the nineteenth and twentieth centuries.